Safety and tolerability of bosentan in the management of pulmonary arterial hypertension - Kari E Roberts; Ioana R Preston (Dove Medical Press, 2009)
Kari E Roberts, Ioana R PrestonPulmonary, Critical Care and Sleep Medicine, Tufts Medical Center, Boston, Massachusetts, USAAbstract: Endothelin receptor antagonism has emerged as an important therapeutic approach in pulmonary arterial hypertension (PAH). Bench to bedside scientific research has clearly shown that endothelin-1 (ET-1) is over-expressed in several forms of pulmonary vascular disease and plays an important pathogenetic role in the development and progression of PAH. Oral endothelin receptor antagonists (ERAs) have been shown to improve exercise capacity, functional status, pulmonary hemodynamics, and delay the time to clinical worsening in several randomized placebo-controlled trials. Bosentan, the first oral ERA, was approved in 2001 and since that time it has established a strong record of safety and efficacy in PAH. More recently, two additional ERAs, ambrisentan and sitaxsentan, have been approved for use. The objective of this review is to evaluate the available evidence supporting the efficacy, pharmacology, safety and tolerability, and patient-focused perspectives for bosentan, the first approved ERA for PAH. Ongoing and forthcoming randomized trials are also highlighted including the application of bosentan in combination with other PAH therapies.Keywords: bosentan, endothelin receptor antagonists, pulmonary arterial hypertension